Factors associated with dislocation after total hip arthroplasties performed for nontraumatic osteonecrosis of the femoral head: a multicenter cohort study of 5,983 hips - Seneki Kobayashi; Nobuhiko Sugano; Wataru Ando; Wakaba Fukushima; Kyoko Kondo; Takashi Sakai (Acta Orthopaedica)
Background and purpose: Nontraumatic osteonecrosis of the femoral head (ONFH) patients are at a higher dislocation risk after primary total hip arthroplasties (THAs) than osteoarthrosis patients. It has not been clear how large prosthetic heads should be to reduce dislocation. A nationwide multicenter follow-up cohort study of THAs performed for ONFH aimed to evaluate risk factors associated with dislocation and whether larger head size could reduce the dislocation risk. Methods: A multivariable logistic regression model analyzed factors associated with dislocation in 5,983 THAs performed for ONFH between 1996 and 2022 with a median of 7.1 (0.5–27)-year follow-up. Patient age at surgery was 52 years and BMI was 22.9, as medians. A posterior approach was employed in 59%. The head diameter was 22 mm in 4%, 26 mm in 15%, 28 mm in 24%, 32 mm in 36%, and ≥ 36 mm in 21%. Results: 288 THAs (4.8%) dislocated. Younger (1st quartile, ≤ 41 years) patient age (odds ratio [OR] 1.45 CI [95% confidence interval] 1.02–2.07 vs. 2nd quartile), higher BMI (OR 1.05, CI 1.02–1.08 per 1), posterior approach (OR 3.33, CI 1.96–5.56 vs. anterior or anterolateral approach, OR 2.27 CI 1.59–3.23 vs. lateral approach), and smaller heads were identified as risk factors. However, ≥ 36-mm heads were not different from 32-mm heads (OR 1.06 CI 0.69–1.63). Conclusion: Risk factors associated with dislocation were younger patient age, higher BMI, posterior approach, and smaller heads; however, 32-mm heads were large enough to reduce dislocation.